Determinants of SARS-CoV-2 infection across three sentinels sites in Benin during 2021: A multicentric surveillance study. - Aurore Atchade; Anges Yadouleton; Marc Fiogbe; Daleb Abdoulaye Alfa; Emmanuel Yovo; Jean-Yves Le Hesran; Sandrine Hounsa; Cédric Bationo; Antía Figueroa-Romero; Jean Gaudart; Raquel González; Emmanuel Bonnet; et al. (PLOS Global Public Health)
Trial registration NCT06170320 (retrospectively registered on December 21, 2023).